(untitled) (Revista de Crítica Literaria Latinoamericana, 2010)
Starting in the 1940s, and several decades before the proposals on bilingual education in Peru, José María Arguedas advocated the importance and usefulness of alphabetizing the school-age population in their respective mother tongues (mainly Quechua and Aimara) before moving to an imposed use of Spanish. This article highlights the fundamental place education held in Arguedas’ broad progressive vision of Andean cultures and the development of Peru as a modern nation.